Adenoid cystic carcinoma of the head and neck: Patterns of recurrence and implications for intensity‐modulated radiotherapy. Issue 1 (12th October 2022) - Gao, Robert W.; Routman, David M.; Harmsen, William S.; Ebrahimi, Sasha; Foote, Robert L.; Ma, Daniel J.; Neben‐Wittich, Michelle; McGee, Lisa A.; Patel, Samir H.; Moore, Eric J.; Choby, Garret W.; Tasche, Kendall K.; et al.
Abstract: Background: We seek to inform radiotherapy (RT) delivery for adenoid cystic carcinoma of the head and neck (ACC) by evaluating RT techniques and recurrence patterns. Methods: We identified patients with ACC treated with curative‐intent RT from 2005 to 2021. Imaging was reviewed to determine local recurrence (LR). Results: Ninety‐one patients were included. The 5‐year LR risk was 12.2% (6.6–22.7). One patient each experienced a marginal and out‐of‐field recurrence. Patients receiving >60 Gy postoperatively had a 5‐year LR risk of 0% compared to 10.7% (4.2–27.2) with ≤60 Gy. Those receiving 70 and <70 Gy definitively had a 5‐year LR risk of 15.2% (2.5–91.6) and 33.3% (6.7–100.0), respectively. No patients had regional nodal failure. Conclusions: Modern, conformal RT for ACC results in low rates of LR. Doses >60 and 70 Gy may improve control in the postoperative and definitive settings, respectively. Elective nodal treatment can be omitted in well‐selected patients.